2020
DOI: 10.1002/ps.5741
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and herbicidal activity against barnyard grass of novel diarylmethanone O‐(2,6‐bis((4,6‐dimethoxypyrimidin‐2‐yl)oxy)benzoyl)oximes

Abstract: BACKGROUND: Pyribenzoxim is an excellent herbicide that can effectively control barnyard grass. However, there are few reports of its structural analogs and structure-activity relationship (SAR), which makes pyribenzoxim an isolated case. Here, a series of diarylmethanone oxime esters characterized by pyridine heterocycles were designed and synthesized for herbicidal screening and SAR investigation against barnyard grass.RESULTS: At greenhouse treatment concentrations of 1.17-37.5 ∼g mL −1 , the title compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Researchers aim to achieve rapid and efficient synthesis and screening of compounds, which is a common objective in this field. Building upon our extensive research experience, our group previously proposed the “plug-in molecules method”, which significantly enhanced pesticide creation efficiency. Considering the potential of combining diphenyl ether , with pyridine , to generate highly active molecules; we synthesized a series of aryloxy pyridine ethyl ketones as plug-in molecules in the initial stage. Various derivatives can be rapidly produced through various carbonyl reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers aim to achieve rapid and efficient synthesis and screening of compounds, which is a common objective in this field. Building upon our extensive research experience, our group previously proposed the “plug-in molecules method”, which significantly enhanced pesticide creation efficiency. Considering the potential of combining diphenyl ether , with pyridine , to generate highly active molecules; we synthesized a series of aryloxy pyridine ethyl ketones as plug-in molecules in the initial stage. Various derivatives can be rapidly produced through various carbonyl reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Various derivatives can be rapidly produced through various carbonyl reactions. Several studies have demonstrated the effectiveness of this method in developing novel pesticides. , …”
Section: Introductionmentioning
confidence: 99%
“…However, when esterified with other fatty alcohols or phenol, there is a dramatic decrease in its herbicidal activity. ,,, Moreover, pyribenzoxim, an oxime esterification product of bispyribac acid, has proven successful as a light-activated herbicide, altering some characteristics of bispyribac-sodium, such as application period and safety. ,, Other oxime esters have also exhibited good herbicidal performance. , Previously, we synthesized diaryl oxime esters of bispyribac acid bearing a pyridine moiety, exhibiting excellent herbicidal activity in greenhouse and field conditions. These compounds function as pro-herbicide activated via both enzyme-catalyzed hydrolysis and photolysis . Inspired by the interesting differences between alkyl and oxime esters, this study aims to replace oxime esters with simpler phenolic esters (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous herbicides, with approximately 20 modes of actions (MOA), have been discovered and marketed from the 1950s to the 1990s . Examples of herbicidal inhibiting actions include protoporphyrinogen oxidase (PPO), , acetohydroxyacid synthase (AHAS), , acetyl-CoA carboxylase (ACCase), 4-hydroxyphenylpyruvatedioxygenase (HPPD), and many others.…”
Section: Introductionmentioning
confidence: 99%